Implementation of Cleanliness, Health and Environmental Sustainability Guidelines in Restaurants around the Southern Java Crossing Route in Ciamis Regency - Ita Maemunah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the extent to which restaurants on the southern route of Java in Ciamis district implement standard health protocols for Cleanliness, Health, Safety and Environmental Sustainability (CHSE) in order to prevent the spread of the COVID-19 outbreak. This standard health protocol refers to the health guidebook in hotels and restaurants (CHSE) that has been issued and published by the Ministry of Tourism and Creative Economy. This research was conducted as a measuring tool as a control reference in the implementation of the CHSE health protocol, especially in restaurants in the southern route of Java, Ciamis district. This study used a survey research method approach with data collection techniques through interviews; observation, and literature study. The population in this study were restaurants located on the southern route of Java in Ciamis Regency with a non-random sampling technique, namely accidental sampling. The results of this study indicate that the implementation of general guidelines and specific guidelines for CHSE health protocols is still not going well.